The screening of microorganisms antagonistic to phytopathogens - Andrews, John H. (Pesquisa Agropecuaria Brasileira, 1992)
There are two general options for screening potential biocontrol agents to a plant pathogen: first, microbes can be tested for antagonism under controlled conditions (in the laboratory and/or in a growth chamber or greenhouse), followed by assay of the promising isolates under uncontrolled conditions in the field for final evaluation. This approach offers convenience and efficiency, standardization and reproducibility of test conditions, and the opportunity to directly examine the antagonist/pathogen interaction. However, tests under controlled conditions may fail to detect antagonism or may be poor predictors of biocontrol activity under field conditions. Second, microbes can be tested for activity under uncontrolled conditions, directly in the field, without preliminary assay. This approach offers rigorous, realistic appraisal of biocontrol potential. However, it poses several logistical constraints even if micro-plots are used, it may not be representative of activity at other times or locations, and it offers no clue as to the underlying mechanism. Both approaches have advantages and disadvantages and choosing either involves compromises. Any screen may be case-specific and may be valid only for those conditions imposed by the protocol. Which strategy will ultimately provide for the optimal evaluation, offering the highest predictability per unit cost invested in time and material, remains to be determined.